Teatro performativo na escola: experiências de docência, pesquisa e criação reveladas pela prática - Saraiva, Wellington Silva (2025)
This master's degree thesis presents a set of academic productions in the form of a “portfolio”, consisting of three articles-reports of artistic-pedagogical experiences in Performative Theater, carried out based on practices with high school students at the Professor Onélio Porto State School of Professional Education. The decision to write academic texts came about when, during the course and together with the research group Laboratório de Pesquisas em Drama (LaPeDra/UFC/CNPQ), I identified an approach to the Practice as Research approach. By understanding a research production throughout a trajectory, we sought to recover and rework such experiences in contextualized writings according to the questions that instigated them, producing thematic research excerpts with the aim of submitting them for publication in journals in the area, thus circulating such writings. From the introduction, which locates the research trajectory, follows the article entitled “Practiced Territories”, which exposes the creation of dramaturgy in performative theater based on the territory, guided by Feral (2008) and Carreira (2012); then the article “Performative theater: possibilities for a problematizing education” dialogues with Feral (2008, 2009, 2011, 2015, 2020) and Freire (1986, 1996, 2002, 2019) and finally the text “Aguapé: performative actions in the anthropocene”, which deals with the issues of the anthropocene based on the interactions, ecologies and archaeologies of a workshop with students, in dialogue with Feral (2008), Cordeiro (2023), Reis (2022) and Sermon (2021). The texts communicate research of a qualitative methodological nature with traces of a research-training approach and practice as research, having used data production tools, photos, notes, theater workshop classes and bibliographic research. Both the theater practices developed and studied, as well as the experience of writing about these practices, were guided by the concept of performative theater, and each article brings a complementary concept to this concept, supporting and particularizing the theater experience. The production as a whole situates the practices in performative theater as an experience that makes it possible to discuss theater making and issues necessary to exist and resist in the world, as well as affirming a teaching practice as research, which collaborates both with the knowledge constructed with the students and in the academic production of what is researched and produced in the classroom in the Art discipline.